(untitled) (Clinics, 2013)
OBJECTIVE: The purpose of this study was to compare aerobic function [anaerobic threshold (%VO2-AT), respiratory compensation point (%VO2-RCP) and peak oxygen uptake (VO2peak)] between physically active patients with HIV/AIDS and matched controls and to examine associations between disease status, poor muscle strength, depression (as estimated by the profile of mood states questionnaire) and the aerobic performance of patients. METHODS: Progressive treadmill test data for %VO2-AT (V-slope method), RCP and (VO2peak) were compared between 39 male patients with HIV/AIDS (age 40.6±1.4 years) and 28 male controls (age 44.4±2.1 years) drawn from the same community and matched for habitual physical activity. Within-patient data were also examined in relation to CD4+ counts (nadir and current data) and peak isokinetic knee torque. RESULTS: AT, RCP and (VO2peak) values were generally similar for patients and controls.Within the patient sample, binary classification suggested that AT, RCP and (VO2peak) values were not associated with either the nadir or current CD4+ count, but treadmill test variables were positively associated with peak isokinetic knee torque. CONCLUSION: The aerobic performance of physically active patients with HIV/AIDS is generally well conserved. Nevertheless, poor muscle strength is observed in some HIV/AIDS patients, which is associated with lower anaerobic power and (VO2peak), suggesting the possibility of enhancing the aerobic performance of patients with weak muscles through appropriate muscle-strengthening activities.